2009
DOI: 10.1186/1479-5876-7-62
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and beta cell protective effects of andrographolide analogue for diabetes treatment

Abstract: BackgroundWhile all anti-diabetic agents can decrease blood glucose level directly or indirectly, few are able to protect and preserve both pancreatic beta cell mass and their insulin-secreting functions. Thus, there is an urgent need to find an agent or combination of agents that can lower blood glucose and preserve pancreatic beta cells at the same time. Herein, we report a dual-functional andrographolide-lipoic acid conjugate (AL-1). The anti-diabetic and beta cell protective activities of this novel androg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 42 publications
2
73
0
4
Order By: Relevance
“…Andrographolide modulates physiological functions of diverse drug metabolising enzymes in liver and other peripheral organs as well (Pekthong et al 2008), and binds covalently with cellular metabolites and enzymes (Xia et al 2004). Andrographolide-lipoic acid conjugate possesses andrographolide like and longer lasting antidiabetic activity in mice (Zhang et al 2009). Therefore, it could as well be that the observed beneficial effects of andrographolide on memory functions and AChE and antioxidative enzymes in the brain observed in this study are due to its conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…Andrographolide modulates physiological functions of diverse drug metabolising enzymes in liver and other peripheral organs as well (Pekthong et al 2008), and binds covalently with cellular metabolites and enzymes (Xia et al 2004). Andrographolide-lipoic acid conjugate possesses andrographolide like and longer lasting antidiabetic activity in mice (Zhang et al 2009). Therefore, it could as well be that the observed beneficial effects of andrographolide on memory functions and AChE and antioxidative enzymes in the brain observed in this study are due to its conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…Andrographolide, natural bicyclic diterpenoid lactones, is an active constituent of Andrographis paniculata. Experimental studies demonstrated diverse pharmacological effects of andrographolide including anti-inflammatory, antihyperglycemic, hepatoprotective and anticancer properties (Lin et al, 2009;Zhang et al, 2009). Previous studies from our laboratory demonstrated the antigenotoxic, pro-apoptotic and anti-inflammatory potential of andrographolide in experimental animal models Shanmugam et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sambiloto merupakan salah satu tanaman obat yang mempunyai banyak khasiat antara lain sebagai anti diabetes (ZHANG et al, 2009), anti mikrob (XU et al, 2006), anti kanker (CHENG et al, 2007). Tanaman sambiloto mengandung beberapa senyawa kimia antara lain terpenoid, flavonoid, alkane, keton, aldehid, mineral (kalium, kalsium, natrium), asam kersik, dan dammar (RAO et al, 2004).…”
Section: Pendahuluanunclassified